CAPERS-LRD-z9: A Gas-enshrouded Little Red Dot Hosting a Broad-line Active Galactic Nucleus at z = 9.288 - Anthony J. Taylor; Vasily Kokorev; Dale D. Kocevski; Hollis B. Akins; Fergus Cullen; Mark Dickinson; Steven L. Finkelstein; Pablo Arrabal Haro; Volker Bromm; Mauro Giavalisco; Kohei Inayoshi; Stéphanie Juneau; et al. (The Astrophysical Journal Letters)
We present CAPERS-LRD-z9, a little red dot (LRD) that we confirm to be a z = 9.288 broad-line active galactic nucleus (BLAGN). First identified as a high-redshift LRD candidate from PRIMER NIRCam photometry, follow-up NIRSpec/PRISM spectroscopy of CAPERS-LRD-z9 from the CANDELS-Area Prism Epoch of Reionization Survey (CAPERS) has revealed a broad 3500 km s ^−1 full width at half-maximum H β emission line and narrow [O iii ] λλ 4959, 5007 lines, indicative of a BLAGN. Based on the broad H β line, we compute a canonical black hole mass of ${log}\,(M_{{\rm{BH}}}/M_{\odot })=7.58± 0.15$ , although full consideration of systematic uncertainties yields a conservative range of $6.65\lt {log}\,(M_{{\rm{BH}}}/M_{\odot })\lt 8.50$ . These observations suggest that either a massive black hole seed or a lighter stellar remnant seed undergoing periods of super-Eddington accretion is necessary to grow such a massive black hole in ≲500 Myr of cosmic time. CAPERS-LRD-z9 exhibits a strong Balmer break, consistent with a central AGN surrounded by dense (∼10 ^10 cm ^−3 ) neutral gas. We model CAPERS-LRD-z9 using Cloudy to fit the emission redward of the Balmer break with a dense-gas-enshrouded AGN and bagpipes to fit the rest-ultraviolet emission as a host-galaxy stellar population. This upper limit on the stellar mass of the host galaxy (<10 ^9 M _⊙ ) implies that the black hole to stellar mass ratio may be extremely large, possibly >5% (although systematic uncertainties on the black hole mass prevent strong conclusions). However, the shape of the UV continuum differs from typical high-redshift star-forming galaxies, indicating that this UV emission may also be of AGN origin; hence, the true stellar mass of the host may be still lower.